Minimal Residual Disease in Acute Lymphoblastic Leukemia: Technical and Clinical Advances - Della Starza, Irene; Chiaretti, Sabina; De Propris, Maria S.; Elia, Loredana; Cavalli, Marzia; De Novi, Lucia A.; Soscia, Roberta; Messina, Monica; Vitale, Antonella; Guarini, Anna; Foà, Robin (Frontiers in Oncology, 2019)
Introduction: Acute lymphoblastic leukemia (ALL) is the first neoplasm where the assessment of early response to therapy by minimal residual disease (MRD) monitoring has proven to be a fundamental tool to guide therapeutic choices. The most standardized methods to study MRD in ALL are multi-parametric flow cytometry (MFC) and polymerase chain reaction (PCR) amplification-based methods. Emerging technologies hold the promise to improve MRD detection in ALL patients. Moreover, novel therapies, such as monoclonal antibodies, bispecific T-cell engagers, and chimeric antigen receptor T cells (CART) represent exciting advancements in the management of B-cell precursor (BCP)-ALL. Aims: Through a review of the literature and in house data, we analyze the current status of MRD assessment in ALL to better understand how some of its limitations could be overcome by emerging molecular technologies. Furthermore, we highlight the future role of MRD monitoring in the context of personalized protocols, taking into account the genetic complexity in ALL. Results and Conclusions: Molecular rearrangements (gene fusions and immunoglobulin and T-cell receptor-IG/TR gene rearrangements) are widely used as targets to detect residual leukemic cells in ALL patients. The advent of novel techniques, namely next generation flow cytometry (NGF), digital-droplet-PCR (ddPCR), and next generation sequencing (NGS) appear important tools to evaluate MRD in ALL, since they have the potential to overcome the limitations of standard approaches. It is likely that in the forthcoming future these techniques will be incorporated in clinical trials, at least at decisional time points. Finally, the advent of new powerful compounds is further increasing MRD negativity rates, with benefits in long-term survival and a potential reduction of therapy-related toxicities. However, the prognostic relevance in the setting of novel immunotherapies still needs to be evaluated.